MEDAL UPAMIĘTNIAJĄCY KRÓLEWSKĄ KORONACJĘ JANA III SOBIESKIEGO I MARII KAZIMIERY W KRAKOWIE POCHODZĄCY Z 1676 ROKU. UWAGI IKONOGRAFICZNE - Rokita, Jan Gustaw (Studia Europaea Gnesnensia, 2018)
The author of the article discusses in depth ten works of art (prints, numismatic pieces, sculptures) which demonstrate iconographic consistency with the obverse or reverse of the said medal. As the author argues, the medallionist sought both to reflect current events in Cracow and commemorate the beginning of the propitious reign of Jan III Sobieski and Maria Kazimiera, which would benefit the people of the Commonwealth (bear fruits), which is why he used well-known representations from 17th-century compendia of emblems as well as 16th- and 17th-century coinage and medals.